Analysis of Gut Bacterial and Fungal Microbiota in Children with Autism Spectrum Disorder and Their Non-Autistic Siblings - Retuerto, Mauricio; Al-Shakhshir, Hilmi; Herrada, Janet; McCormick, Thomas S.; Ghannoum, Mahmoud A. (Nutrients, 2024)
Autism Spectrum Disorder (ASD) is a multifactorial disorder involving genetic and environmental factors leading to pathophysiologic symptoms and comorbidities including neurodevelopmental disorders, anxiety, immune dysregulation, and gastrointestinal (GI) abnormalities. Abnormal intestinal permeability has been reported among ASD patients and it is well established that disturbances in eating patterns may cause gut microbiome imbalance (i.e., dysbiosis). Therefore, studies focusing on the potential relationship between gut microbiota and ASD are emerging. We compared the intestinal bacteriome and mycobiome of a cohort of ASD subjects with their non-ASD siblings. Differences between ASD and non-ASD subjects include a significant decrease at the phylum level in Cyanobacteria (0.015% vs. 0.074%, p < 0.0003), and a significant decrease at the genus level in Bacteroides (28.3% vs. 36.8%, p < 0.03). Species-level analysis showed a significant decrease in Faecalibacterium prausnitzii, Prevotella copri, Bacteroides fragilis, and Akkermansia municiphila. Mycobiome analysis showed an increase in the fungal Ascomycota phylum (98.3% vs. 94%, p < 0.047) and an increase in Candida albicans (27.1% vs. 13.2%, p < 0.055). Multivariate analysis showed that organisms from the genus Delftia were predictive of an increased odds ratio of ASD, whereas decreases at the phylum level in Cyanobacteria and at the genus level in Azospirillum were associated with an increased odds ratio of ASD. We screened 24 probiotic organisms to identify strains that could alter the growth patterns of organisms identified as elevated within ASD subject samples. In a preliminary in vivo preclinical test, we challenged wild-type Balb/c mice with Delftia acidovorans (increased in ASD subjects) by oral gavage and compared changes in behavioral patterns to sham-treated controls. An in vitro biofilm assay was used to determine the ability of potentially beneficial microorganisms to alter the biofilm-forming patterns of Delftia acidovorans, as well as their ability to break down fiber. Downregulation of cyanobacteria (generally beneficial for inflammation and wound healing) combined with an increase in biofilm-forming species such as D. acidovorans suggests that ASD-related GI symptoms may result from decreases in beneficial organisms with a concomitant increase in potential pathogens, and that beneficial probiotics can be identified that counteract these changes.